Implementation of Sharia Compliance in Sharia Hotels Based on Consumer Perspectives - Hayat, Syam Bahrul; Rozali, Rozmita Dewi Y; Juliana, Juliana; Prawito, Ponsen Sindu (Iqtisad: Journal of Islamic Economic and Civilization, 2025)
The background of this research is based on the phenomenon of the not yet optimal application of sharia compliance in sharia hotels. In addition, there are still many people who do not understand and understand the difference from sharia hotels to conventional hotels. This study aims to measure the assessment or level of implementation of Sharia Compliance in Islamic hotels in the city of Bandung, namely Sharia Daarul Jannah Cottage, Rumah Tawa and Orange Home’s Sharia hotels based on sharia hotel consumer perspectives. The research data was obtained from hotel consumer respondents totaling 100 people. The research method used is quantitative descriptive with data analysis techniques using descriptive statistics. The characteristics of sharia hotel consumers have an average marital status married to 31 to 30 years old. The results of the study showed that the evaluation or level of implementation of Sharia Compliance in three sharia hotels was included in the criteria of good, for the dimensions that received the lowest rating, namely the service dimension. While for other dimensions such as product and management dimensions are quite good. However, in this study the implications of the need for increased shari'ah compliance in sharia hotels, especially in some aspects of service, hotel management, MUI DSN regulation and fatwa on managing sharia hotels.